Impact of the COVID-19 epidemic on cancer burden and cancer care in Slovenia - Žagar, Tina (Radiology and oncology (Ljubljana), 2022)
In Slovenia, cancer care services were exempt from government decrees for COVID-19 containment. Nevertheless, cancer control can be impacted also by access to other health services and changes in health-seeking behaviour. In this follow up study, we explored changes in cancer burden and cancer care beyond the first months after the onset of the COVID-19 epidemic.Materials and methods. We analysed routinely collected data for the period January 2019 through July 2022 from three sources: (1) pathohistological and clinical practice cancer notifications from two major cancer centres in Ljubljana and Maribor (source: Slovenian Cancer Registry); (2) referrals issued for oncological services (source: e-referral system); and (3) outpatient appointments and diagnostic imaging performed (source: administrative data of the Institute of Oncology Ljubljana – IOL). Additionally, changes in certain clinical and demographic characteristics in patients diagnosed and treated during the epidemic were analysed using the Hospital-Based Cancer Registry of the IOL (period 2015–2021).Results. After a drop in referrals to follow-up cancer appointments in April 2020, in June-August 2020, there was an increase in referrals, but it did not make-up for the drop in the first wave; the numbers in 2021 and 2022 were even lower than 2020. Referrals to first cancer care appointments and genetic testing and counselling increased in 2021 compared to 2019 and in 2022 increased further by more than a quarter. First and follow-up outpatient appointments and cancer diagnostic imaging at the IOL dropped after the onset of the epidemic in March 2020 but were as high as expected according to 2019 baseline already in 2021. Some deficits remain for follow-up outpatients’ appointments in surgical and radiotherapy departments. There were more CT, MRI and PET scans performed during the COVID-19 period than before. New cancer diagnoses dropped in all observed years 2020, 2021 and until July 2022 by 6%, 3% and 8%, respectively, varying substantially by cancer type. The largest drop was seen in the 50-64 age group (almost 14% in 2020 and 16% in 2021), while for patients older than 80 years, the numbers were above expected according to the 2015–2019 average (4% in 2020, 8% in 2021).Conclusions. Our results show a varying effect of COVID-19 epidemic in Slovenia for different types of cancers and at different stages on the patient care pathway – it is probably a mixture of changes in health-seeking behaviour and systemic changes due to modifications in healthcare organisation on account of COVID-19. A general drop in new cancer cases reflects disruptions in the pre-diagnostic phase and could have profound long-term consequences on cancer burden indicators.
Keywords: cancer; covid-19; delay in diagnosis; prepozne diagnoze; rak